2017
DOI: 10.1101/164392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective membrane dynamics emerging from curvature-dependent spatial coupling

Abstract: Membrane curvature has been recognized as an active participant of fundamental biological processes including vesicular transport and organelle biogenesis, but its effects on membrane remodeling are typically local. Here we show membrane curvature plays a critical role in propagating cortical waves and modulating mesoscale dynamics in living cells. We employ a membrane shape-dependent mechanochemical feedback model to account for the observed oscillatory travelling waves of Cdc42, F-BAR proteins and actin.We d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…We hypothesized that mechanical factors including osmotic pressure or the adhesion state of the metaphase cortex could determine the occurrence of metaphase waves. We have previously shown that application of hypotonic shock to increase the osmotic pressure of cells could instantly inhibit wave assembly and propagation (Wu et al, 2017). To determine whether increased cell adhesion could lead to higher probability of metaphase waves, we transfected cells with dominant active Rap1 Q63E, which maintains the adherent cell shape during mitosis (Dao et al, 2009).…”
Section: Adhesion-dependent Mitosis Invokes Metaphase Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that mechanical factors including osmotic pressure or the adhesion state of the metaphase cortex could determine the occurrence of metaphase waves. We have previously shown that application of hypotonic shock to increase the osmotic pressure of cells could instantly inhibit wave assembly and propagation (Wu et al, 2017). To determine whether increased cell adhesion could lead to higher probability of metaphase waves, we transfected cells with dominant active Rap1 Q63E, which maintains the adherent cell shape during mitosis (Dao et al, 2009).…”
Section: Adhesion-dependent Mitosis Invokes Metaphase Wavesmentioning
confidence: 99%
“…The microscope was equipped with an iLAS2 motorized TIRF illuminator (Roper Scientific) and an Evolve 512 EMCCD camera (Photometrics, 16 bit, pixel size 16 mm). SRIC imaging was performed as previously described using a mercury lamp (X-Cite 200DC, 200 W, Excelitas, Waltham, MA) as the light source (Wu et al, 2017…”
Section: Time-lapse Microscopymentioning
confidence: 99%
“…To test whether FBP17 represents part of the positive feedback for clathrin to be synchronized into waves, we knocked down FBP17 and CIP4, the only two Toca family F-BAR proteins expressed in RBL-2H3 cells according to our RNA sequencing data (Figure S6A). Double knockdown of FBP17 and CIP4, but not single knockdown of FBP17 alone, inhibited the formation of Cdc42 waves (15.4%, n=52 cells, compared to ~90% in controls) (Wu et al, 2017), and all of the clathrin waves (0%, n=52 cells) (Figure 5A). We also visualized clathrin dynamics in cells co-transfected with Cdc42-T17N, a dominant negative mutant of Cdc42.…”
Section: Resultsmentioning
confidence: 99%
“…FI741227: GCAGAAGTGGTTGCTCCTGACTGGCATAT, and FI741228: GGTGTTCCTGATTACCAAGTATGGTTATA), mCherry-CLC (Addgene #27680), AP2μ2-mCherry (Addgene #27672), Eps15-mCherry (Addgene #27696), EGFP-EPSIN1 (Addgene #22228), EGFP-Glut4 (cloned from Addgene #18087), TfR-pHuji (Addgene #61505), Dynamin1-K44A-EGFP (Addgene #22197) AP1σ1 (Lei Lu, Nanyang Technological University), mRFP-CBD (Addgene #26733), Dynamin1-GFP (Addgene #22163), Tks5-GFP (B. Diaz, Sanford-Burnham Medical Research Institute), GFP-FCHo1, GFP-CLC, Endophilin2-GFP, mCherry-actin, and mCherry-FBP17 (P. De Camilli, Yale University), Lyn-tailed mCherry Cdc42-T17N (cloned from Myc Cdc42-T17N from P. De Camili, Yale University), SHIP1 shRNA, CIBN-pmGFP, mCherry-CRY2-iSH2 PI3K , mCherry-Grp1-PH, GFP-PH(TAPP1)-PH(TAPP1), iRFP-N-WASP, mCherry-SHIP1, and FBP17-EGFP were previously described (Xiong et al, 2016). CIP4 shRNA, FBP17 shRNA were previously described (Wu et al, 2017). …”
Section: Methodsmentioning
confidence: 99%